High resolution transmission electron microscopy study on polyacrylonitrile/carbon nanotube based carbon fibers and the effect of structure development on the thermal and electrical conductivities. (November 2015) - Newcomb, Bradley A.; Giannuzzi, Lucille A.; Lyons, Kevin M.; Gulgunje, Prabhakar V.; Gupta, Kishor; Liu, Yaodong; Kamath, Manjeshwar; McDonald, Kenneth; Moon, Jaeyun; Feng, Bo; Peterson, G.P.; Chae, Han Gi; et al.
Abstract: Polyacrylonitrile (PAN) and PAN/carbon nanotube (CNT) based carbon fibers at various CNT content have been processed and their structural development was investigated using high resolution transmission electron microscope (HR-TEM). In CNT containing carbon fibers, the CNTs act as templating agents for the graphitic carbon structure development in their vicinity at the carbonization temperature of 1450 °C, which is far below the graphitization temperature of PAN based carbon fiber (>2200 °C). The addition of 1 wt% CNT in the gel spun precursor fiber results in carbon fibers with a 68% higher thermal conductivity when compared to the control gel spun PAN based carbon fiber, and a 103% and 146% increase over commercially available IM7 and T300 carbon fibers, respectively. The electrical conductivity of the gel spun PAN/CNT based carbon fibers also showed improvement over the investigated commercially available carbon fibers. Increases in thermal and electrical conductivities are attributed to the formation of the highly ordered graphitic structure observed in the HR-TEM images. Direct observation of the graphitic structure, along with improved transport properties in the PAN/CNT based carbon fiber suggest new applications for these materials.